SISTEM PEMERIKSAAN ALAT PEMADAM KEBAKARAN PERSPEKTIF MILK AL DAULAH: STUDI PADA PEMADAM KEBAKARAN BANDA ACEH - Nurvira, Khairatun Aini; Maulana, Muhammad; Umur, Azmil (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2022)
The Banda Aceh City Fire and Rescue Service must ensure that fire extinguishers are well maintained and can be used at any time in an emergency. Fire extinguishers are state property that are useful for the community. Therefore, the author aims to conduct research to find out how fire extinguishers are inspected at the Banda Aceh City Fire and Rescue Service, as well as what Milk al Daulah's perspective is regarding checking fire extinguishers at the Banda Aceh City Fire and Rescue Service. This research uses a sociological juridical method with a qualitative research type, and data was obtained using interview techniques and documentation. Based on the research results, it was found that, first, inspection and maintenance of fire extinguishers at the Banda Aceh City Fire and Rescue Service was carried out by checking and warming up the engine, checking lubricants and fuel, checking the condition of tires, checking the braking system, checking equipment completeness. fire extinguisher, electrical system inspection, exterior maintenance, water tank drain, and vehicle roadworthiness test. Maintenance is carried out regularly at certain time intervals. Usually every 3 months, 6 months or 1 year. Depends on manufacturer's instructions, vehicle model and components used. Second, the Banda Aceh City Fire and Rescue Service is responsible for inspecting fire extinguishers. So that these tools function and are used properly when a fire disaster occurs. Maintaining fire extinguishers provides benefits to the community. The Banda Aceh city fire and rescue service as the regional government has done its job well in carrying out inspections of fire extinguishers, therefore this is in accordance with the concept of milk al-daulah